Suomen olympia-akatemian 18. istunto 16.10.2004 Joensuussa - Suomen olympia-akatemia. Istunto 2004 : Joensuu); Hintikka, Matti; Tikander, Vesa, 1966-; Ylimaa, Markus; Suomen olympiakomitea ([Helsinki] : [Suomen olympiakomitea], 2005)
Summaries.
Kansinimeke: Suomen olympia-akatemian 18. istunto Joensuussa 16.10.2004.
Keywords: olympialiike; urheilu; huippu-urheilu